Islam And The Secular State K Negotiating The Future Of Shari'a - An- Naim, Abdullahi Ahmed (Cambridge, Mass. Harvard University Press, 2009)
What Should be the Place of Shari'a Islamic religous law in Predominantly Muslim Socities of the world? In This ambitious and topical book, a Muslim Scholar anf human rights activist Envisions a Postive and sustainable Role For Shari'a based on a profound rethinking of the relationship between religion and the secular state in all socities
1- Introduction: Why Muslims Need A Secular State
2- Islam, The State, And Politics In Historical PErspective
3- Constitutionalism, Human Rights, And Citizenship
4- India: State Seculaeisim and Communal Violence
5- Turkey: Contradiction Of Authoritarian Secularism
6- Indonesia: Realities Of Diversity And Prospects Of Pluralism
7- Conclusion: Negotiating The Future Of Shari'a
Keywords: Islam and secularism; Islam and state; Islamic law; Religious pluralism - Islam